Mahantha Ampavatina Kambagiri - Ampavatina Kambagiri, Mahantha (My University, 2023)
Abstract The rise in integration of renewable energy sources is reducing the power system in ertia, causing an issue with the frequency stability of the system. Low inertia makes the system more sensitive to disturbances, where even a small disturbance can lead to large frequency deviations which can go outside the frequency band. Ancillary services are needed as frequency regulation is becoming more and more important and prices for frequency regulation go up in the Nordic region. This thesis investi gated the potential of providing ancillary services using the Vehicle-to-Grid (V2G) technology in a low-inertia power system dominated with renewable energy sources. In this thesis, a preliminary aggregated V2G model was developed, that can pro vide ancillary services such as Frequency Containment Reserve for disturbances, up-regulation (FCR-D up) and Fast Frequency Reserve (FFR) according to the technical requirements laid out by ENTSO-E. The delays pertaining to communica tion and hardware response were considered. Considering the Simulink V2G model as a reference for validation and comparison of results, an aggregated user-written model was built in PSS®E. Prequalification testing of the aggregated V2G model in both Simulink and PSS®E for the provision of FCR-D up indicated that they fulfilled the technical requirements and qualified to provide 100% of their capacity. However, when the communication and hardware response delays were introduced, the prequalified capacity reduced as the delays increased. No delays were considered for the provision of FFR as fixed activation times are stated in the requirements. The prequalification tests for FFR showed that the models fulfilled all the requirements and were qualified to provide FFR service. The developed V2G models were implemented in power system models to provide frequency support in Simulink and PSS®E. Two scenarios with different inertia, rep resenting the present and future power system, were considered to assess the impact of the models. When providing FCR-D support, the frequency nadir improved when the delays were short for both higher and lower inertia cases in Simulink and PSS ®E. However, as the delays increased, they resulted in frequency overshoots, which induced frequency oscillations in the lower inertia cases. When providing FFR support to the power system models, the frequency nadir im proved for both higher and lower inertia cases. The improvement was observed to be higher for the low inertia case as compared to the higher inertia with the FFR quantity and the disturbance being the same in both Simulink and PSS®E.
Keywords: Ancillary service, V2G technology, user-written modelling, prequalification testing, Nordic power system